Cost efficiency in commercial banking in Poland. Linear ordering approach - Niedziółka, Paweł; Korzeb, Zbigniew (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: Previous research has primarily focused on the impact of operational efficiency on bank profitability. An in-depth review of the literature indicates that there is a lack of studies aimed at identifying the characteristics of banks with similar levels of cost efficiency. Aim: The aim of the article is to identify clusters of banks with similar profiles, given the level of operating costs relative to the scale and profitability of operations. Results: Operational efficiency is positively related to bank profitability, and economies of scale manifest themselves in the form of relatively higher cost efficiency of large credit institutions. The results confirm the validity of the management strategy of the abrupt reduction of operating costs in commercial banks and create premises for supervisory authorities to prepare the expected (optimal) scenario of banking sector structure evolution and adjust to it the regulatory policy.